The phenomenology of motivation - R. André; J. Romão; F. Azevedo; M. Gonçalves; C. Sereijo; R. Saraiva; M. Croca; M. Abreu (European Psychiatry, 2022)
Introduction The concept of motivation pervades our professional and personal lives. Motivation is almost impossible to be observed directly, it is a construct for the interpretation of a behaviour that “calls the attention”.